Intervensi Edukatif dan Skrining Hipertensi sebagai Upaya Deteksi Dini Penyakit Tidak Menular di Wilayah Pedesaan - Intan Kumalasari; Nisrina Khansa Nabila; Farach Labita Anissa Putri; Anisa Kurniawati; M. Daffa Afanda; Hanifuddin Abdul Rohman (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Hypertension is a common non-communicable disease with a high prevalence and a significant risk of severe complications if not detected and managed early. In Dusun 02, Tanjung Baru Village, under the jurisdiction of the Tanjung Baru Health Center in Ogan Komering Ulu Regency, many residents are unaware of their blood pressure status and lack knowledge about risk factors and prevention. This community service activity aimed to increase public awareness through health education and conduct blood pressure screening for early detection of hypertension. The methods included educational sessions on hypertension, healthy lifestyle promotion, and on-site blood pressure checks for targeted residents. The results demonstrated an increase in participants’ understanding of hypertension and identified several individuals with elevated blood pressure who had not been previously diagnosed. In conclusion, educational intervention combined with direct screening is an effective approach to raise awareness and enable early detection of hypertension in rural communities.